Carcinoma In Situ Is Significantly Underdetected by Prenephroureterectomy Ureteroscopy in the Management of Upper Tract Urothelial Cancers. (15th January 2015) - Gillan, Angela; El-Mokadem, Ismail; Rai, Bhavan; Lang, Stephen; Alcorn, Jason; Shams ud din, Altaf; Dasgupta, Ranan; Biyani, Chandra Shekhar; Nabi, Ghulam
Abstract : Objective . Diagnostic reliability of prenephroureterectomy ureteroscopy (PNU) for the detection of upper tract carcinoma in situ (CIS) remains unproven in particular and underreported in general. Methods . Patients who underwent radical nephroureterectomy (RNU) in a large multicentre retrospective study for upper tract transitional cell carcinoma (UT-TCC) between January 2002 and December 2013 were identified from our hospitals databases. PNU appearances, stage, and grade of ureteroscopic biopsy were compared with final histology results of RNU to assess the diagnostic reliability of PNU for carcinoma in situ (CIS). Results . Three hundred patients underwent RNU for UT-TCC. 106 (106/300; 35.3%) of the cohort had PNU using white light with biopsies taken in most (92/106; 86.7%). Postnephroureterectomy histology of the cohort showed CIS in 65 (65/300; 21.6%) patients. Thirty nine of patients with CIS (39/65; 60%) had prenephroureterectomy ureteroscopy biopsies. Out of ten patients with CIS on ureteroscopic biopsies, six did not show CIS on final histopathology (6/10; 60%). Moreover, grading and staging on PNU biopsies of obvious tumours showed a significant nonconcordance with final histopathology of RNU specimen ( P = 0.02 ) . Overall survival was also shorter in patients with CIS compared with those without; this showed strong statistical significance ( P = 0.004 ) . Conclusions . There is a high incidence of CIS in upper tract with significant underdetection and discordance rate between the histopathology of biopsy samples obtained by white light PNU and resected specimen of radical nephroureterectomy. The presence of concomitant CIS and high stage disease in the upper tract TCC carried a poor prognosis following radical nephroureterectomy.